2021
DOI: 10.3233/cbm-201709
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA testis-specific transcript, Y-linked 15 (TTTY15) promotes proliferation, migration and invasion of colorectal cancer cells via regulating miR-29a-3p/DVL3 axis

Abstract: BACKGROUND: Long non-coding RNA testis-specific transcript, Y-linked 15 (TTTY15) is oncogenic in prostate cancer, however its expression and function in colorectal cancer remain largely unknown. METHODS: Paired colorectal cancer samples/adjacent tissues were collected, and the expression levels of TTTY15, miR-29a-3p and disheveled segment polarity protein 3 (DVL3) were examined by quantitative real-time polymerase chain reaction (qRT-PCR); TTTY15 shRNA and overexpression plasmids were transfected into HT29 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…In addition, the knockdown of DVL3 expression has been found to control the progression of esophageal squamous cell carcinoma, inhibit cell proliferation and promote the apoptosis of tumor cells (27). Moreover, a recent study has revealed that testis-specific transcript, Y-linked 15 downregulates DVL3 expression in colorectal cancer tissues and promotes the proliferation, migration and invasion of colorectal cancer cells (32). The findings of the present study revealed that the expression levels of DVL3 were upregulated in OSCC cell lines, and a Co-IP assay confirmed Figure 5.…”
Section: Discussionsupporting
confidence: 85%
“…In addition, the knockdown of DVL3 expression has been found to control the progression of esophageal squamous cell carcinoma, inhibit cell proliferation and promote the apoptosis of tumor cells (27). Moreover, a recent study has revealed that testis-specific transcript, Y-linked 15 downregulates DVL3 expression in colorectal cancer tissues and promotes the proliferation, migration and invasion of colorectal cancer cells (32). The findings of the present study revealed that the expression levels of DVL3 were upregulated in OSCC cell lines, and a Co-IP assay confirmed Figure 5.…”
Section: Discussionsupporting
confidence: 85%
“…Intriguingly, miR-30c has also been involved in the infection by Porcine epidemic diarrhea virus (PEDV), a member of the Alphacoronavirus family: the virus engages the SOCS1/miR-30c axis to escape IFN-l-mediated antiviral immune responses ( Wang C. et al, 2020 ). miR-29a-3p is involved in gastric and breast cancer, as well as colorectal cancer and hepatocarcinoma ( Li Y. et al, 2020 ; Wang J. et al, 2020 ; Zheng et al, 2020 ; Pan et al, 2021 ; Qu et al, 2021 ); interestingly, miR-29a has been considered as a potential therapeutic target for HIV eradication, because of its binding to Nef viral protein, critical for viral persistence and release, and binding to the 3′UTR region of the HIV genome, mediating the transport of the virus to P-bodies ( Ahluwalia et al, 2008 ; Nathans et al, 2009 ). MiR-15b is probably one of the most extensively studied in relation to cancer pathways, since it shares most of its sequence, including the seed region, with the well-known miR-15a that together with the clustered miR-16 were the first miRNAs related to a tumor, the chronic lymphocytic leukemia ( Calin et al, 2002 ); recently, both loci, miR-15a/16-1 and miR-15b/16-2, have been shown to drive the pathogenesis of acute myeloid leukemia ( Lovat et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, knocking down TTTY15 reduces H 2 O 2 -induced cardiomyocyte injury via modulating the miR-98-5p/CRP axis [ 29 ]; TTTY15 can promote hypoxia-induced vascular endothelial cell injury by down-regulating miR-186-5p [ 30 ]. Importantly, TTTY15 is also involved in regulating the proliferation, differentiation, apoptosis and other biological processes of cancer cells [ 9 , 11 , 31 ]. Our previous study reports that TTTY15 up-regulates disheveled segment polarity protein 3 (DVL3) expression by adsorbing miR-29a-3p, thus promoting the malignancy of colorectal cancer cells [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, TTTY15 is also involved in regulating the proliferation, differentiation, apoptosis and other biological processes of cancer cells [ 9 , 11 , 31 ]. Our previous study reports that TTTY15 up-regulates disheveled segment polarity protein 3 (DVL3) expression by adsorbing miR-29a-3p, thus promoting the malignancy of colorectal cancer cells [ 11 ]. Another study reports that TTTY15 promotes CDK6 and FN1 expressions by adsorbing let-7, therefore promoting PCa cell proliferation [ 9 ].…”
Section: Discussionmentioning
confidence: 99%